Effect of Motivation, Attitude Lecturer on The Performance of Lecturer And Improved Quality of Education Case Study: Bogor Agricultural University (IPB) - Suratni Suratni; Musa Hubeis; Iman Santoso (Jurnal Manajemen, 2015)
The results of the analysis showed a direct influence on the motivation of faculty performance by 32.8 % and 5.1 % of the increase in the quality of education. This means that the motivation is strong enough influence on the performance and the lecturer, but did not give a significant effect on improving the quality of education. The attitude of the lecturer gives a direct influence on the performance of lecturers by 55% and 34.4% of the increase in the quality of education. Faculty performance direct impact on improving the quality of education was 46.3%. This means that the attitude of the lecturer gave a strong influence on the performance improvement of the quality of education faculty, faculty performance while giving a strong influence on the improvement of the quality of education. Through faculty performance, motivation of an indirect effect on improving the quality of education at 0.1518 (15,18%), while the attitude of lecturers provide indirect influence on improving the quality of education at 0.2546 (25,46%).